Outcome of Ponseti Casting in Synromic Club Feet (Journal of Pakistan Orthopaedic Association, 2023)
Objective: To determine the effectiveness of Ponseti casting in syndromic clubfootStudy Design: Quasi experimental studyPlace and duration of study: Department of Orthopedics, from January 2020 to December 2021.Methodology: Children of either sex, having clubfoot and other congenital abnormalities, less than one year age, without previous intervention with cast or surgical were included and with previous sessions of casting, previous surgeries, parents unwillingness were excluded. Photographs taken and Pirani score performed before start of casting. Weekly casting was done and documented. TA tenotomy was done in some feet and last cast performed. Last documentation and Pirani scoring was done. Follow up was done on 3 and 6 months. Recurrence and surgical procedure requirements documented. All data was compiled on SPSS version 20.Results: 50 children were included. 35 males and 15 females. 40 bilateral and 10 unilateral feet. High Pirani scoring was recorded before Ponseti Casting. Different number of casts were required and TA tenotomies done. Pirani score showed improvement but requiring more casts that idiopathic clubfeet. Pre and post-Ponseti mean Pirani score was 4.05 (S.D: ±0.82) and 2.0 (S.D: ±0.5) respectively with statistical significant difference (p